Characteristics of the level of athletes' sports preparedness in freestyle wrestling - Bakytbek Konakbayev; Raisa Bekembetova; Omirzhan Bekturganov; Mukhtar Yeskaliyev; Dinara Zhunisbek (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: This article deals with the issue of a comprehensive approach to researching the level of athletic fitness of freestyle wrestlers based on the results of competitive activity, in the laboratory and training process. Objective: Using a comprehensive research approach to assess the technical and tactical skills, as well as the level of functional capabilities of athletes in freestyle wrestling. Methodology: Competitive activity was analyzed to evaluate technical and tactical skill. The heart rate and lactate concentration level were recorded during the preparation for competitive wrestling and the recovery period. An in-depth complex examination was performed, which included assessment of anthropometric indices, registration of the main parameters of external respiration and gas exchange, cardiovascular system. Results: The indicators of recovery processes during the training process and competitive activity were obtained to assess the level of preparation of freestyle wrestlers, where a number of shortcomings of their training were revealed. Discussion: Criteria for evaluating competitive loads on the basis of determining the concentration of lactate in the blood were developed. The obtained information allowed to determine the level of preparedness of athletes in freestyle wrestling, as well as the readiness to conduct the next competitive bout Conclusions: Comparative analysis of competitive activity has shown that it is necessary to correct the algorithm of modes of training processes. When conducting training of low aerobic power to perform the necessary volume while observing the individual mode as for the level of lactate and heart rate.